Efektivitas Program Pusaka Sakinah dalam Menurunkan Angka Stunting pada Keluarga di Kabupaten Kutai Timur: Studi di KUA Kecamatan Sangatta Utara - Fathul Bari, Muhammad; Duraesa, Muhammad Abzar; Andaryuni, Lilik (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
The aim of this research is to determine the effectiveness of the Pusaka Sakinah Program in reducing the incidence of stunting and the supporting and inhibiting factors in its implementation within families in the Office of Religious Affairs (KUA) in the North Sangatta District. The research method employed is qualitative, utilizing a Field Research type with a sociological-juridical approach. Data collection techniques include observation, interviews, and documentation, and the data analysis technique begins with data condensation, followed by data presentation, concluding with data interpretation while using data validity techniques. The results indicate that the effectiveness of the Pusaka Sakinah program in reducing the incidence of stunting within families is attributed to programs provided by the North Sangatta KUA, such as the Secret Marriage Learning Program, Counseling, Mediation, Support, Advocacy, Consultation, and the Joint Services for Indonesian Family Resilience Program. Inhibiting factors include a shortage of religious counselors and program implementers, while supporting factors include support from related government agencies such as the National Family Planning Board (BKKBN), community health centers (Puskesmas), and educational institutions for the Pusaka Sakinah program in reducing the incidence of stunting within families in the North Sangatta District.